2016
DOI: 10.18203/2320-6012.ijrms20160053
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure as the initial manifestation of takayasu's arteritis

Abstract: On inquiry there was history of orthopnea and paroxysmal nocturnal dyspnea.There was no history of cough, hemoptysis, fever, joint pain, headache, malaise, weight loss, loss of appetite or any other systemic manifestation. No history of tuberculosis or tuberculosis contact.Patient consulted a chest physician initially and was suspected of having bronchial asthma and started on formoterol and budesonide rotahaler for the same. ABSTRACTTakayasu's arteritis is a rare systemic, inflammatory large vessel vasculitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…One recent case report describes a teenage girl who presented with acute heart failure due to myocarditis, however she had preceding arm claudication, systemic and cutaneous manifestations in the preceding one year [10]. In another case report, a 27-year-old female who presented with features of heart failure was found to have severe pulmonary hypertension and dilated cardiomyopathy together with pulse and blood pressure difference between two arms [11]. This patient also did not have any constitutional symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…One recent case report describes a teenage girl who presented with acute heart failure due to myocarditis, however she had preceding arm claudication, systemic and cutaneous manifestations in the preceding one year [10]. In another case report, a 27-year-old female who presented with features of heart failure was found to have severe pulmonary hypertension and dilated cardiomyopathy together with pulse and blood pressure difference between two arms [11]. This patient also did not have any constitutional symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Our case presented with hypertension and features of congestive cardiac failure. Khan et al also reported a case of TA with features of congestive cardiac failure [14].…”
Section: Ta Is Currently Categorized As a Systemic Granulomatous Largevessel Vasculitis In The Chapel Hill Consensus Conferencementioning
confidence: 94%